Ejes de soporte para accesibilidad digital para la Política de Inclusión de UFRN (Research, Society and Development, 2020)
The Accessibility Policy elaboration of the Federal University of Rio Grande do Norte (UFRN) involved working groups convened by the university administration. The working groups were organized by accessibility dimensions in Article 3 of the Statute of Persons with Disabilities (Law No. 13.146/2015). A working group for Digital Accessibility was created, seeking to reflect on technological, communication and informational barriers that Information and Communication Technologies can impose on people with disabilities. This group was composed by specialists from academic and technical areas of the university, ranging from administrative to academic units, such as the Superintendence of Informatics (SINFO), Digital Metropolis Institute (IMD), Secretariat of Distance Education (SEDIS), Superintendence of Communication (COMUNICA), among others. This group produced a draft on Digital Accessibility for the university Accessibility Policy, along with a draft action plan for digital artifacts produced or purchased by the institution, such as web pages, mobile applications, and computer programs. This paper aims to report experiences of this working group in the preparation of these endeavors, as well as the results obtained. For this, an action research was conducted with the participants of the working group throughout their work process, gathering empirical data of qualitative nature, contextualized in the institution reality. One of the main results was an action plan model structured in areas of training, communication and technological development to promote Digital Accessibility at UFRN.